Efficacy of Lemon and Lemongrass Essential Oils on Stress among Parents of Children with Intellectual Disabilities - Sharon Kosgey; John Okoth; Benard Juma (Evidence-Based Nursing Research)
Context: Essential oils act as alternative medicine and have great therapeutic benefits. Oils derived from Lemon (Citrus limon) and Lemongrass (Cymbopogon citratus) have great importance for stress reduction. No holistic studies compare their chemical composition, essential oil constituents, and efficacy in stress control. Parents who have children with intellectual disabilities (ID) go through the highest levels of stress, which can lead to significant psychological and physical health problems. Therefore, there is a great need for effective stress management interventions that are non-pharmacological. If widely spread interventions work, it can lead to reduced chemical usage rates.